EFFECTS OFF BEET JUICE SUPPLEMENTATION ON PERFORMANCE IN ANAEROBIC EXERCISES - Coelho da Silva, Adriano Junior; Gheno dos Santos, Gricielle; de Ross Rosa, Leonardo; Conde, Simara Rufatto (Revista Uningá, 2020)
There is a growing demand for nutritional supplements that increase the production of nitric oxide (NO). One of the ways of obtaining NO through nitrate ingestion. A nitrate supplementation aimed at increasing performance and recent in the history of exercise physiology, the first publication on nitrate supplementation was in 2007 and in 2009 on nitrate supplementation through beet juice. The aim of the present study was to evaluate the effect of non-performance beet juice supplementation on anaerobic exercises of soccer practicing athletes. A sample of eight junior athletes from a football club. These were supplemented with 500ml / day of beet juice for seven consecutive days. They performed force testicles using an extensor chair to evaluate the effect of supplementation. The increase in number of repetitions observed not in this study was not significant (p> 0.05). The mean BMI found was 22.56 ± 1.09 kg / m2, 87.5% were classified as eutrophic, and 12.5% ​​were overweight. Inadequate intakes of calories, calcium, B9, potassium, fiber and magnesium, as well as a hypoglycemic dietary pattern, such as signs of insufficiency, may impair the performance and outcome of this study. Although there is evidence that beet juice supplementation improves performance in anaerobic exercises, no significant improvement was observed without strength testing.